Medical and nursing students' views and attitudes of objectives structured clinical examination as a comprehensive performance assessment - Kartajaya, Fatin Arryana Nasution (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2012)
This is a cross sectional survey study investigating the medical and nursing students' views and attitudes of Objective Strnctured Clinical Examination (OSCE) as a comprehensive perfom1ance assessment. A sample of 172 students was selected from medical and nursing students who had experience an OSCE participate in this study. A set of questionnaire was used for data collection. The questionnaire consists of demographic data and four component of OSCE. The component measured are medical and nursing students' views and attitudes towards the OSCE, students' preparation prior the OSCE, perception aftennath the OSCE and perception to the overall OSCE process. The hypotheses of the study were tested using independent t test through SPSS version 19 for statistical analysis. The results indicated that there is no significance difference between medical and nursing students' views and attitudes towards the OSCE (p= 0.449). However, the result shows that there is a significance difference between medical and nursing students' views and attitudes towards the OSCE preparation and perfonnance (p= 0.001). There is also a significance difference between medical and nursing students' views and attitudes towards the OSCE aftermath (p= 0.023) and the overall OSCE process (0.003).